ANALISIS KEUNTUNGAN USAHA WARUNG KOPI MERAPI DI DUSUN PETUNG, DESA KEPUHARJO, KECAMATAN CANGKRINGAN, KABUPATEN SLEMAN, DAERAH ISTIMEWA YOGYAKARTA - Ewaldus Raju; Ignatius Suprih Sudrajat; Susi Widiatmi (JURNAL ILMIAH AGRITAS, 2019)
This research was carried out on purpose to determine the profit of Kopi Merapi as Coffee shop. Research hypothesis is Kopi Merapi profitable to developed. The basic method used in this research is a descriptive method. The data used in this research by collecting secondary and primary data in Kopi Merapi in 2018. The method of data analysis used is Revenue Cost Ratio (R/C) by using t test as hypothesis test. The research shows that average production cost monthly of Kopi Merapi in 2018 is IDR141.053.031 with average income monthly in 2018 is IDR183.302.292. The average profit monthly of Kopi Merapi in 2018 is IDR42.249.261. Based on the analysis, Revenue Cost Revenue (R/C) for Kopi Merapi is 1.32. Hypothetical test result shows that the value of t test (2.124) > t table (1.717) with an error rate of 5%. It means that t test analysis is significant. If t test > t table means Ha is accepted and Ho is rejected. Ha is accepted means that Ï€ > 0. Thus, it can be concluded that the proposed hypothetical is accepted. It means that Kopi Merapi profitable to developed.